Microplastic abundance and characterization in the anaerobic co-digestion of food waste and dairy manure - Whitney, Abbey L.; Chomiak, Kristina M.; Babbitt, Callie W.; Eddingsaas, Nathan C.; Tyler, Anna Christina (Frontiers in Sustainable Food Systems, 2025)
Microplastics (MP) are an emerging contaminant in organic waste recycling, yet their occurrence and fate in anaerobic digestion (AD) systems remain poorly understood due to challenges in isolating MP from complex matrices. This study developed and validated a novel extraction method using peroxide oxidation and an EDTA–Triton X-100 solution that achieved >96% recovery without polymer degradation. This method was applied to characterize MP in manure, digester effluent (digestate), and lagoon storage at a full-scale food waste–manure co-digestion facility. MP were consistently detected across all sources, with concentrations ranging from 120 MP kg−1 (manure) to >3,300 MP kg−1 (lagoon). Abundance was highly variable over time, shaped by feedstock composition and digester management practices. The MP observed likely stemmed from multiple pathways, including food waste inputs, packaging residues, on-farm sources, atmospheric deposition, and fragmentation of larger plastics during digestion. Polyethylene terephthalate (PET) fibers dominated across all samples. These findings provide the first quantitative evidence of microplastic (MP) occurrence throughout the AD process and highlight how management decisions influence contamination. By advancing extraction methods and generating new field-scale data, this study establishes a foundation for assessing the risks of MP release from AD systems to agricultural soils and downstream ecosystems.